2013
DOI: 10.48550/arxiv.1309.4646
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Probing Magnetic Fields using the Giant Metrewave Radio Telescope

Abstract: Presentamos las primeras observaciones espectropolarimétricas que aplican síntesis de medidas de rotación a datos interferométricos obtenidos con el Giant Metrewave Radio Telescope (GMRT) a 610 MHz. La espectropolarimetría requiere la medición de un gran número de efectos sistématicos instrumentales para lograr calibrar sus efectos -un reto técnico al que se enfrentan los instrumentos precursores del SKA. Nuestros datos completamente calibrados permiten medir el pico de la profundidad de Faraday a nivel de sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…For these real data, many sources are visible in the Q and U skew images, which are displayed on the same scales, and show a larger skew in Stokes U. This skew is also associated with M51 itself, which Farnes, Green, & Kantharia (2013) and Mulcahy et al (2014) showed to be unpolarized at low radio frequencies. The increased skew is therefore most likely the result of polarization leakage.…”
Section: Application To Real Lofar Datamentioning
confidence: 83%
“…For these real data, many sources are visible in the Q and U skew images, which are displayed on the same scales, and show a larger skew in Stokes U. This skew is also associated with M51 itself, which Farnes, Green, & Kantharia (2013) and Mulcahy et al (2014) showed to be unpolarized at low radio frequencies. The increased skew is therefore most likely the result of polarization leakage.…”
Section: Application To Real Lofar Datamentioning
confidence: 83%
“…For Faraday tomography of extragalactic objects, such as nearby galaxies, low-frequency data has not been as successful. Mulcahy et al (2014) and Farnes et al (2013) used observations from LOFAR at 150 MHz and the Giant Meterwave Radio Telescope at 610 MHz respectively to search for polarized emission from M51, but did not detect significant polarization. Faraday tomography has been successfully applied to nearby galaxies at higher frequencies (e.g.…”
Section: Recent Observationsmentioning
confidence: 99%